Variation of floral traits in Thai rice germplasm (Oryza sativa) - Saran Khumto (2018)
© 2018, Springer Science+Business Media B.V., part of Springer Nature. Floral traits play an important role in mating systems in flowering plant species. In rice, variation in floral traits has been established in a wide range of germplasm, but the variability of floral traits in Thai rice remains uncharacterized. Sixty-seven rice varieties that are cultivated throughout the country and two accessions of common wild rice were evaluated for nine floral traits to assess the extent of variation, and the differentiation of floral traits among groups of rice (improved rice varieties, selected traditional varieties, local traditional varieties and wild rice). The range of variation of all traits examined in Thai rice varied within the exte nt of variation that has been reported in other rice germplasm. Most of the floral traits observed in Thai rice have mean values similar to other reports, except in stamen traits, percentage of stigma exertion and the length of spikelet, which exhibited higher mean values than other germplasm investigations. Since these floral traits have a large contribution on outcrossing potential, Thai rice might have a greater chance of natural outcrossing compared to other cultivated rice germplasm. There is no clear differentiation in floral traits among groups of cultivated rice, but there are obvious differences in most of the floral traits between cultivated rice varieties and common wild rice, illustrated in the transformation of rice floral structures during domestication. The results have implications for outcrossing and spontaneous gene flow as well as a potential use in the parental lines for hybrid rice seed production.